Assessing the factors of resilience of private consumption in the Euro Area - Deroose, Servaas; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
Understanding the behaviour of private consumption is crucial for the assessment of the economic situation in the short and the medium term. As the largest expenditure component of GDP, household spending plays a central role in the cyclical fluctuations of activity around its long-term growth path. According to consumption theory, households endeavour to smooth their spending over the life-cycle, a behaviour which should contribute to dampen the strength of cyclical downswings. However, recent developments in private consumption in the euro area have been disappointing. Since 2001, growth in private consumption has been persistently sluggish and has been much weaker than in some other EU countries or in the USA. Furthermore, after years of a declining trend, households have responded to deteriorating growth conditions with a rise in their saving rate in 2001-02. Since then their saving rate has remained broadly constant.
Economic Papers